Manajemen Strategik dalam Lembaga Pendidikan Madrasah Aliyah untuk Meningkatkan Pendidikan yang Bermutu - Aminullah, Aminullah; Firmansyah, Mohammad; Febrianto, Febi; Rofik, Moh; Fikri, Ahmad Rausan; Ni’am, Muhammad Durrin; Alwahedi, Mohammad Abdul Aziz (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyse the implementation of strategic management to improve the quality of education at Madrasah Aliyah Ihyaul Ulum Guntung. The main focus is on how planning, execution, and evaluation of managerial strategies are carried out by the madrasah to achieve quality education. The method used is a qualitative approach with a case study. Data were collected through interviews, observations, and documentation, then analysed using data reduction, data presentation, and conclusion drawing techniques. The results show that strategic management is applied through the formulation of clear vision and mission, strengthening teachers' competencies, and optimising the role of the madrasah head as a leader. These strategies have a positive impact on discipline, academic achievement, and community participation in supporting madrasah activities. The findings emphasise the importance of planned and sustainable strategic management to enhance the quality of education, particularly in Islamic educational institutions aimed at building students' character and competencies.